The languages of the Andes - Adelaar, Willem F. H. (Cambridge University Press, 2004)
The Languages of the Andes documents in a single volume the indigenous languages spoken and formerly spoken in this linguistically rich region, as well as in adjacent areas. Grouping the languages into different cultural spheres, it describes their characteristics in terms of language typology, language contact, and the social perspectives of present-day languages. The authors provide both historical and contemporary information, and illustrate the languages with detailed grammatical sketches. Written in a clear and accessible style, this book will be a valuable source for students and scholars of linguistics and anthropology alike.